Pengembangan Model Pembelajaran Peradilan Mini dalam Meningkatkan Aktivitas Belajar PKn Siswa - Zainul Fuad Siregar (Jurnal Didaktika Pendidikan Dasar, 2023)
Citizenship education is a learning content that prepares students to be able to face the challenges of the 21st century as a nation. The aim of this research is to design a mini learning development model to increase student activity. This learning model is a miniature of the conference process which is designed so that students compete in arguments to solve problems. The development research method was carried out using ADDIE research (Analysis, Design, Development, Implementation and Evaluations) and was applied in 23 students class V of SDN 01 Muara Satu as samples. There are two instruments used: 1) a validation sheet to assess the feasibility of the learning model given to two experts and 2) an observation sheet to assess student activities which consists of six activities. The resulting data was analyzed using a percentage index. The results that 1) the learning model is feasible with an average of 71.5% and can be implemented in class and 2) this model can increase student learning activity, that the average student activity has increased from 72.80% to 87.10 % or an increase of 14.3%. So the conclusion that the mini lesson model can increase student learning activities